Knowledge, attitude, and practice on food safety culture among kitchen employees of Malaysian government hospitals - Abdul Rashid, Suhaila; Ariffin, Hashim fadzil; Sanny, Maimunah; Ungku Zainal Abidin, Ungku Fatimah; Abdul Mutalib, Noor Azira; Mohd Izani, Hasni Falina (Universiti Teknologi MARA, 2020)
The objective of the present study was to use a questionnaire on knowledge, attitude, practice (KAP) to assess food safety culture in government hospital kitchens. Four different government hospitals kitchens with food safety management system (FSMS) in place located in Selangor and Federal Territory of Kuala Lumpur were evaluated. The questionnaires were used to assess the basic food hygiene knowledge, attitude and practice of the hospital food handlers and samples were collected from the selected critical sampling location (CSL). The results suggest that food hygiene and safety control is always considered as important and prioritized in most of the hospitals. Attention needs to be given to KAP on time and temperature control that are indicating a lower score to have a total positive prevailing FS-culture.